Comparative study between poorly differentiated thyroid cancer and anaplastic thyroid cancer: real-world pathological distribution, death attribution, and prognostic factor estimation - Kun Zhang; Xinyi Wang; Tao Wei; Zhihui Li; Jingqiang Zhu; Ya-Wen Chen; Ya-Wen Chen; Ya-Wen Chen; Ya-Wen Chen; Ya-Wen Chen (Frontiers in Endocrinology, 2024)
BackgroundThe clinic-pathological boundary between poorly differentiated thyroid cancer (PDTC) and anaplastic thyroid cancer (ATC) is unclear due to a wide spectrum of histopathological features and the rarity of the disease. In addition to that, with the highest mortality rate and non-standard treatment modality, the PDTC/ATC population has not been subjected to comprehensive description and comparison with the extent of histological characteristics, therapeutic response, prognostic factors, and death attribution analysis.MethodA total of 4,947 PDTC/ATC patients from 2000 to 2018 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan–Meier survival curve estimation and Cox proportional hazard regression were applied.ResultsOverall, the 5- and 10-year DSS for PDTC were 71.9% and 68.0%, respectively, whereas the 5- and 10-year OS are 59.3% and 51.2%, respectively. The median survival time for ATC patients was 3 months with 1-year OS being 26.9% and 1-year DSS being 31.2%. During the follow-up period, 68.1% of the PDTC/ATC cohort were dead, 51.6% of which were attributed to thyroid malignancies and 16.5% to non-thyroid causes. The top three common non-thyroid causes of death were miscellaneous cancers, lower respiratory system disease, and heart disease. The histological feature of papillary thyroid cancer (PTC) was the leading pathological category for PDTC patients (51.7%), whereas 76.7% of ATC patients’ pathological feature was characterized as unidentifiable. Sarcoma histological characteristics found in ATC cases suffer the highest overall mortality (vs. PTC, HR = 2.61, 95% CI 1.68–4.06, P < 0.001). Older age unidentifiable histology feature, more advanced AJCC N1b, AJCC M1, and SEER stage, tumor size larger than 5 cm, and more invasive tumor extension were independent bad outcome predictors.ConclusionThe populational analysis of the PDTC/ATC cohort has provided reliable support for better understanding of the difference between PDTC and ATC cases and the guidance of clinical practice and further studies.